Reliability and Validity of the Turkish Reintegration to Normal Living Index in Amputees - Demirdel, Senem; Bayramlar, Kezban Yigiter (SAGE Publications Inc.)
In our country, outcome measures are needed to evaluate the results of occupational therapy in amputees. This study aimed to cross-culturally adapt the Reintegration to Normal Living Index (RNLI) and to evaluate the reliability and validity of a Turkish version of the RNLI. The Turkish version of the RNLI was applied to 120 amputees. Cronbach’s alpha coefficient and the intraclass correlation coefficient (ICC) were used to determine internal consistency and test–retest reliability, respectively. Criterion validity was assessed using Short Form 36 (SF-36). The Turkish version of the RNLI presented reliable results in repeated assessments (ICC =.88), and the internal consistency of the RNLI was high (Cronbach’s α coefficient =.89). A statistically significant relationship was found between RNLI and SF-36 (p <.05). The Turkish RNLI is a reliable and valid tool to evaluate the level of reintegration to normal living for amputees. © The Author(s) 2020.
Keywords: occupational therapy; participation; social participation